Collectivistic Norms and International Entrepreneurship: A Tale of Two Clans, the Wenzhounese from China and the Chettiars from India - TAN, Wee Liang (Institutional Knowledge at Singapore Management University, 2013)
There is a need in the field of international entrepreneurship for ideas and theory developed from within the SME field and less reliance on that developed in the field of international business and large firms. This paper seeks to address this gap but examining the two groups of international entrepreneurs from China and India: the Wenzhou people and the Chettiars. These two groups began internationalising in the past before globalisation became a norm in the colonial days and before when ships sailed along trade winds. It seeks to draw lessons from these two groups: their collectivistic norms and practices.